Examining the effect of physical activity on life skills: the role of exercise on nutrition - Mustafa Arıcı; Mert Ayrancı; Abdurrahim Kaplan; Mehmet İsmail Tosun (Turkish Journal of Kinesiology)
Understanding the effects of physical activity on the life skills of university students and how exercise shapes their eating habits is critical for the development of healthy lifestyles. This study aimed to examine the relationships between life skills, exercise habits, and nutritional behaviors of students enrolled in the Faculty of Sport Sciences, involving the participation of 222 male and 143 female students. This study utilized a correlational survey model to examine the relationships between life skills, exercise habits, and nutritional behaviors. The research data were collected with the Personal Information Form, the Life Skills Scale for Sport and the Healthy Lifestyle Behaviors Scale. The findings revealed that female students had higher scores in life skills areas such as communication, leadership and teamwork compared to male students, while male students had higher exercise scores. In addition, a moderate positive relationship was found between exercise and nutrition and exercise had a significant predictive power on dietary habits. These results emphasize the important role of exercise in supporting life skills and healthy lifestyles of university students.